Race, culture, and counselling - Lago, Colin, 1944- (Open University Press, 1996)
The climate, the context and the challenge. Issues of race and power. Towards understanding culture. Cultural barriers to communication. Communication, language and gesture. Western theories of counselling and psychotherapy: intentions and limitations. Non-western approaches to helping. Filmed cases: training aids to the therapeutic process...